Early Grade Reading in South Africa : Policy Research Paper - Kika, Jesal; Crouch, Luis; Dulvy, Elizabeth Ninan; Thulare, Tshegofatso (Washington, DC: World Bank, 2022)
In recent years, there has been significant momentum in prioritizing early grade reading outcomes in South Africa. As an initial first step to stimulate dialogue on how to take early grade reading (EGR) to scale, this policy paper provides a synthesis of previous and existing early grade reading models in South Africa. The overarching aim of this paper is to build an understanding of what we have collectively learned from early grade reading programs that have been implemented in South Africa, start thinking about how the existing education system can be steered toward effective practices found across initiatives to date and in the literature on effective language instruction, and to advocate for regularly measuring the reading fluency and comprehension of young children with established national targets for improvement. The paper also outlines a set of next steps for the South African Government to consider in transitioning from operational research to program implementation.